2177-LB: Mitochondrial Infiltration of Nuclear-Derived circRNA circBirc6 Regulates ATP Synthase Assembly and Fat Differentiation, Linking Energy Metabolism to Obesity - HUANG, YANRUI; ZHU, TIANXIN; LI, YANBING; XIAO, HAIPENG; REN, MENG; SU, SHICHENG (Diabetes (New York, N.Y.), 2025)
Introduction and Objective: Impaired adipocyte differentiation contributes to insulin resistance and obesity-related type 2 diabetes. Mitochondrial dysfunction is central to impaired adipogenesis. This study investigates how nuclear-encoded circRNA circBirc6 regulates mitochondrial function and adipogenesis, and its role in metabolic disorders. Methods: We used obesity and adipose-specific circBirc6 knockdown mouse models, and clinical samples from obese and diabetic patients. CircBirc6 expression in adipocyte mitochondria was analyzed by high-throughput profiling. In vitro, we evaluated circBirc6 overexpression and knockdown effects on mitochondrial function and adipogenesis. Results: CircBirc6 was upregulated in the mitochondria of obese mice, negatively correlating with mitochondrial function and adipogenesis. In knockdown mice, body weight, adipose tissue volume, and insulin sensitivity improved. In patients, circBirc6 expression was elevated in omental WAT from subjects with obesity and diabetes. Overexpression of circBirc6 impaired mitochondrial function and adipogenesis. CircBirc6 binds to ATP5A and ATP5B in mitochondria, affecting ATP synthase assembly. Conclusion: CircBirc6 regulates mitochondrial function and adipogenesis, linking it to obesity-related metabolic disorders, providing a novel therapeutic target.